Resepsi Naskah Masa'il As-Samarqandi Karya Syeikh Abu Laits As-Samarqandi - Supriatna, Agus; Marhadi, Akhmad; Hayunira, Sasadara; Rasiah, Rasiah (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
Information on the acceptance of the text manuscript is essential as a reference for Islamic teaching materials in Nusantara. This article aims to explain the reception of the ancient manuscript entitled